As ressonâncias da literatura popular do nordeste no Romance d`A Pedra do Reino e o Príncipe do sangue do vai-e-volta - Nunes, Geice Peres (2010)
This dissertation studies the influence of Northeastern Brazilian Cordel and oral poetry on Ariano Suassuna s novel Romance d A Pedra do Reino e o Príncipe do Sangue do vai-e-volta. One of our theoretical starting points are Bakhtin's propositions on the novel as a literary gender and Umberto Eco s concept of openness common to some literary works: these theoretical assumptions have been specially useful to understand Suassuna s ability to incorporate into his novel the manifold strata of popular and oral culture, alongside with Western and particularly Iberian culture and poetry. One of our main interest was to seize Suassuna s special handling of Brazilian popular topics and themes, shaping a novel that accomplishes the romantic dream of melting together social and historical data colored by the aural dignity of oral poetry.